Justification of the citizens' right of access to public passenger transport services by the human rights to mobility and equality before the law - Korže, Branko (Lex localis, 2021)
As opposed to authors who strive to justify the right of access to public passenger transport services of citizens predominantly on the principles of justice deriving from social ethics, the authors of this article justify the right of such access on the human rights to mobility and equality before the law, as the rights based on international legal acts, whereas the principles of fairness are used to upgrade the human right to equality and prohibition of discrimination. Based on the rights to mobility and equality before the law, the authors justify an obligation of democratic states to introduce a law to provide for people an adequate access to public passenger transport services at the interurban and urban level. The theoretical findings established herein will serve as a basis to evaluate legal regulations in the selected states (the Republic of Slovenia and the Republic of Croatia), and create proposals to change the same.
Keywords: človekove pravice; dostopnost; enakopravnost; javni prevoz; javni promet; mestni promet; potniški promet; zakonodaja